2021
DOI: 10.3390/s21227638
|View full text |Cite
|
Sign up to set email alerts
|

A Wearable Soft Fabric Sleeve for Upper Limb Augmentation

Abstract: Soft actuators (SAs) have been used in many compliant robotic structure and wearable devices, due to their safe interaction with the wearers. Despite advances, the capability of current SAs is limited by scalability, high hysteresis, and slow responses. In this paper, a new class of soft, scalable, and high-aspect ratio fiber-reinforced hydraulic SAs is introduced. The new SA uses a simple fabrication process of insertion where a hollow elastic rubber tube is directly inserted into a constrained hollow coil, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Additionally, the device still contains rigid structures, which do not interface well with the human body, reducing the comfort and portability of the devices [24]. An examination of 52 wearable devices revealed that a mere 11% of them were classified as fully soft [22,23,[25][26][27]. Within the realm of fully soft wearable devices, flexible textile materials stand as the prevalent solution for ensuring a compliant connection with the user's body [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the device still contains rigid structures, which do not interface well with the human body, reducing the comfort and portability of the devices [24]. An examination of 52 wearable devices revealed that a mere 11% of them were classified as fully soft [22,23,[25][26][27]. Within the realm of fully soft wearable devices, flexible textile materials stand as the prevalent solution for ensuring a compliant connection with the user's body [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“… 12 It should be noted that the use of Exosuits in rehabilitation is a relatively new approach in rehabilitation robotics, and no comparison studies have been completed to date. 7 13 14 …”
Section: Introductionmentioning
confidence: 99%
“… An example of an upper limb exosuit robot described by Hoang et al 7 being worn by a volunteer. Note: The person shown in the picture is not a patient and was taken with the participant’s knowledge and permission.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations